PENGARUH PERSONAL ATTITUDE, SUBJECTIVE NORMS DANPERCEIVED BEHAVIOR CONTROL TERHADAP MINAT PROFESI SEKRETARIS PADA PROGRAM KEAHLIAN ADMINISTRASI PERKANTORAN DI SMK NEGERI 1 SINGARAJA TAHUN AJARAN 2017/2018 - Lulup endah tripalupi; M Rudi Irwansyah (Jurnal Pendidikan Ekonomi, 2018)
This study aimed to know, the influence of Personal Attitude, Subective Norms, and Perceived Behavior Control toward the interest of secretary profession partially and simultaneously on office administration skill program in SMK Negeri 1 Singaraja. The type of this study was causal study. The data was compiled using questionnaire method and documentation method. The analysis of this research used t test, f test and multiple linear regression by using SPSS (Statistical Product and Service Solutions) verson 16.0 for Windows. The result shows that personal attitude has an influence toward the interest of secretary profession, this in shown by the score of t 2.433 with the significant standard 0.017 or significant 0.017 < 0.05. The subjetive norms also gives an influence toward the interest of secretary profession, this is shown by the score of t 26.555 with the significant standard 0.000 or significant 0.000 < 0.05, and perceived behavior control influences the interest of secretary profession. This in shown by the score of t 21.578 with the significant standart 0.000 or significant 0.000 < 0.05. Simultaneously, personal attitude, subjective norms, and perceived behavior control influence the interest of secretary profession on the office administration skill program in SMK Negeri 1 Singaraja in te academic year 2017/2018. This in shown by the resut of f  207.330 with the significant standard 0.000 or significant 0.000 < 0.05